In vitro Study of Different Partitionates of Alstonia scholaris (L.) R.Br. Leaf for Thrombolytic and Membrane Stabilizing Activities (Bangladesh Pharmaceutical Journal, 2018)
Alstonia scholaris (L.) R.Br. is a medicinal herb belonging to the family Apocyanaceae. Locally it is known as Chatim and abundant with ethno-medicinal properties. The crude ethanolic extract of A. scholaris leaves along with its n-hexane, ethyl acetate, dichloromethane and aqueous soluble partitionates were assayed for their probable thrombolytic and membrane stabilizing activities. The activities of the leaf extract were compared to standard drugs, streptokinase for thrombolytic and acetyl salicylic acid for membrane stabilizing activities. In this study, among all extractives the highest thrombolytic activity was exhibited by the crude ethanolic extract (55.33±0.08%) (p < 0.001) as compared to Streptokinase (62.07±0.33%) (p < 0.001). Alternatively, ethanol soluble materials also significantly inhibited the haemolysis of human erythrocyte membrane both in induced by hypotonic solution (83.47±0.15%) (p < 0.001) and by heat (79.82±0.71%) (p < 0.001), respectively as compared to standard acetyl salicylic acid (85.09±0.8%) (p < 0.001) and (80.98±1.34%) (p < 0.001).Bangladesh Pharmaceutical Journal 21(2): 145-149, 2018